The Potential of Tanjung Pinang Seaside Coast as a Blue Economy Model - Zubair Arza; Haria Saputri; Hendra Candra (Journal of Economics and Management, 2026)
This study examines the potential of the Seaside Coast in Tanjung Pinang to be developed through a blue economy approach that integrates environmental sustainability, community participation, and local economic development. The research is motivated by the growing environmental challenges in coastal tourism areas, including plastic pollution, coastal erosion, and unmanaged reclamation, which threaten marine ecosystems and the sustainability of tourism. The novelty of this study lies in its contextual and field-based analysis of how blue economy principles can be practically implemented in small-scale coastal tourism management through community involvement and collaborative governance. This study employed a qualitative case study approach. Data were collected through literature reviews, field surveys, semi-structured interviews with 10 informants, Focus Group Discussions (FGDs) involving 12 participants, and direct observations of tourism and environmental conditions in the coastal area. The data were analyzed using thematic analysis and SWOT analysis to identify strategic issues related to sustainable tourism management. The findings indicate that Seaside Coast has strong potential for blue economy-based tourism development, driven by its strategic location, active local MSMEs, and attractive coastal landscape. However, several challenges remain, including weak institutional coordination, limited environmental awareness, plastic waste pollution, and coastal abrasion. The study also highlights that community participation and stakeholder collaboration are essential factors in supporting sustainable coastal tourism governance. In conclusion, the successful implementation of blue economy principles in Tanjung Pinang depends on integrating environmental management, participatory governance, and sustainable tourism planning to ensure long-term ecological and socio-economic sustainability.